A study on cost reduction for oil and gas industry of MMHE Sdn Bhd / Noor Zahrena Abu Talib - Abu Talib, Noor Zahrena (Faculty of Business and Management, 2010)
This research is about cost reduction implied in the oil & gas company known as Malaysia Marine and Heavy Engineering Sdn Bhd (MMHE SDN BHD) wholly owned subsidiary of MISC Berhad. Oil and gas industry is one of the most well establish with a rapid growth in the potential market in Malaysia, that can lead and contribute and income to the country. Therefore, what is involve in each cost of the production and raw material is calculate accurately. No oil and gas company is currently safe from cost pressures. The financial and economic climate that faces nowadays, forces close scrutiny of the cost bases. However, many oil and gas companies still lack a systematic or structured approach to managing cost. The quickest and surest way to improve profitability is to effectively reduce costs. Each expenditure removed from expenses reports to the bottom line profit. The most difficult approach is to increase sales. While the best corporate strategic and operating plans focus on both, one cannot deny the power of an effective cost reduction program. Cost Reduction are easy to install and can guarantee the results.